Hubungan antara Empati dengan Kekerasan Verbal Pada Siswa/Siswi SMAN X - Ufti Rosyidatun Nisa'; Lena Nessyana Pandjaitan (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
Verbal aggression occurs frequently among adolescents. This behavior can result in negative impact such as; trauma and other psychological losses. This study discusses the relationship between empathy and verbal aggression in high school students. Participants in this study were high school students of class X and class XI. This research is a quantitative study with data collection using a questionnaire. The results indicated that there was no relationship between empathy with verbal aggression (r = 0.141; p = 0.112 0.05) which means that the level of empathy does not affect someone committing verbal aggression. In addition, there were external factors causing verbal aggression, namely joining friends and replying to friends who verbally aggression first. The results of this study suggest students report to the school if they see verbal aggression, so the school can follow up and verbal aggression behavior can be avoided. For the school, it is necessary to respond actively to the perpetrators of aggression that occur between students.